Characterization of internal and external variables of the health food industry in Peru - Medina Shimabukuro, Valeria Midori (2023)
Over the last years, several Latin American consumers have been changing their eating habits, opting for healthier options, and allowing the emergence of healthy fast-food restaurants. This research aims to determine the key variables and actors' developments of healthy fast-food restaurants in the culinary industry within the Lima Metropolitan area. With the participation of a group of local experts familiar with the industry and based on a structural analysis that evaluates the levels of motor skills and dependency, the interrelationship between the actors and variables for the study system was determined. The evidence presents commercial management, communication, lifestyle, age distribution, and sale price as influential variables. The social actors responsible for its management are the suppliers, the customers, and the local healthy community. The value of this study lies in the practical knowledge it offers to the management of healthy restaurants, as well as the possibility of designing and strategic planning of future scenarios for the sector.